Effect of human probiotics on memory, psychological and biological measures in elderly: A study protocol of bi-center, double-blind, randomized, placebo-controlled clinical trial (CleverAge Biota) - Bartos, Ales; Weinerova, Josefina; Diondet, Sofia; Vales, Karel (Frontiers in Aging Neuroscience, 2022)
Background: Gut microbiota may influence brain functions. Therefore, we prepared a study protocol of double-blind, cross-over, randomized clinical trial to find out complex effects of human probiotics on memory, psychosocial and biological measures in the elderly. Methods: We selected eligible participants using an effective way of an electronic questionnaire containing the inclusion and exclusion criteria as well as brief electronic cognitive test. One third of the respondents with the worst cognitive scores of the electronic test are randomized to group A starting with 3-month probiotic intervention and to group B starting with placebo. Both groups change their intervention/placebo status after three months for next three months in a crossover design. Participants refusing longer personal assessments due to Covid-19 pandemic are randomly allocated to one of two subgroups assessed online. Participants in both groups are matched with regard to age, education, gender and cognitive scores of electronic testing at baseline. At three time-points participants are assessed using a neuropsychological battery, self-report measures of mood, a physical fitness test, blood, urine and stool samples and actigraphy. A subset of participants also provide their biological samples and undergo the neuropsychological battery in an extended testing phase three months after study termination to find out a long-term effect of the intervention. Discussion: This is the first trial to address comprehensive effects of probiotics from humans on memory and many other measures in the elderly. We assume that the probiotic group will have better outcomes than the placebo group after the first and the second trimester. We expect that the probiotic effect will persist next three months. Findings will contribute to an interesting area how to improve memory and related psychosocial and other factors in a natural way and will explore the importance of probiotics for overall health in the elderly. Trial registration number at clinicaltrials.gov: NCT05051501.